2002
DOI: 10.1002/rcm.595
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry and high‐performance liquid chromatography study of quantitative and qualitative variation in tarantula spider venoms

Abstract: Animal venoms are important sources of novel pharmacological tools, useful in biochemical characterization of their receptors. Venom quality control, batch-to-batch homogeneity and high reproducibility of venom fractionation and toxin purification are crucial issues for biochemical and pharmacological studies. To address these issues, a study of the variability of tarantula spider venom samples was undertaken. Venom profiles of samples collected from individuals of different age and sex, and from sibling spide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…However, intraspecific variations can also occur as shown recently in Dinoponera quadriceps for which only 48 peptides were shared between colonies out of the more than 300 peptides found in total (Cologna et al 2013). Also, intraspecific variations in venom composition have been observed in snakes, scorpions, tarantulas and cone snails, this variation being linked to geographical distribution (Núñez et al 2009;Shashidharamurthy et al 2002), age (Escoubas et al 2002) or sex (Escoubas et al 1997;Herzig and Hodgson 2009;Herzig et al 2002;Herzig et al 2008). However, it remains unclear whether such variation is a common denominator for all venomous animals or is restricted to some taxa or species.…”
Section: Introductionmentioning
confidence: 87%
“…However, intraspecific variations can also occur as shown recently in Dinoponera quadriceps for which only 48 peptides were shared between colonies out of the more than 300 peptides found in total (Cologna et al 2013). Also, intraspecific variations in venom composition have been observed in snakes, scorpions, tarantulas and cone snails, this variation being linked to geographical distribution (Núñez et al 2009;Shashidharamurthy et al 2002), age (Escoubas et al 2002) or sex (Escoubas et al 1997;Herzig and Hodgson 2009;Herzig et al 2002;Herzig et al 2008). However, it remains unclear whether such variation is a common denominator for all venomous animals or is restricted to some taxa or species.…”
Section: Introductionmentioning
confidence: 87%
“…Significantly less dramatic variations in the peptide complement of injected venoms have been reported for several other organisms, including snakes (Chippaux et al, 1991;Creer et al, 2003;Daltry et al, 1996a,b;Francischetti et al, 2000;MacKessy et al, 2003;Monteiro et al, 1998a,b), spiders (Binford, 2001;Cristina de Oliveira et al, 1999;Escoubas et al, 2002) The α-, ω-conotoxins and s4a have all been previously isolated from the DV and characterized. Underlined peptides are those that are putatively identified in this work by mass matching to published cDNA sequences with predicted modifications.…”
Section: Conus Catus As Determined By Maldi-msmentioning
confidence: 92%
“…Sequence s4b is not included in this and Her, 2000). Variation of the peptide profiles of these other venomous animals has been associated with sex (Binford, 2001;Cristina de Oliveira et al, 1999;Escoubas et al, 2002), diet (Daltry et al, 1996b), age (Escoubas et al, 2002), geography (Binford, 2001;Creer et al, 2003), season (Monteiro et al, 1998b) and venom regeneration time (Pimenta et al, 2003). Studies controlling many of these factors have still observed venom variation, implying that intraspecific differences can be a result of genetic as well as environmental factors (Daltry et al, 1996a;Francischetti et al, 2000;Kalapothakis and Chavez-Olortegui, 1997;Monteiro et al, 1998a,b).…”
Section: Conus Catus As Determined By Maldi-msmentioning
confidence: 99%
“…according to Escoubas et al [15]. All experiments were performed using the saturated α-cyano-4-hydroxycinnamic acid (CCA), dissolved in 50% (v/v) solution of acetonitrile and aqueous 0.2% TFA, as the matrix.…”
Section: Mass Spectrometry (Ms)mentioning
confidence: 99%